2016
DOI: 10.1371/journal.pone.0163848
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Patterns in Tuberculosis Infection; IL-1ra, IL-2 and IP-10 Differentiate Borderline QuantiFERON-TB Samples from Uninfected Controls

Abstract: BackgroundInterferon gamma release assays (IGRAs) do not discriminate between active tuberculosis (TB) and latent TB infection (LTBI), which limit their use in TB endemic areas. Subjects with QuantiFERON-TB (QFT) results around the diagnostic cut-off more likely show inconsistent results on serial testing which makes the interpretation of the assay difficult. We have studied potential biomarkers in patients with various stages of TB infection and with borderline QFT tests compared to those with higher values.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
(42 reference statements)
2
18
1
Order By: Relevance
“…In previous studies IL-2 has been shown to enhance diagnosis of LTBI, particularly in those with borderline QFT results. 19 In addition, IL-2 levels are generally higher in LTBI compared with active TB patients. 20 Our results showing elevation of IL-2 before IFN-γ conversion by QFT suggests IL-2 is a likely marker of early infection leading to subsequent conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies IL-2 has been shown to enhance diagnosis of LTBI, particularly in those with borderline QFT results. 19 In addition, IL-2 levels are generally higher in LTBI compared with active TB patients. 20 Our results showing elevation of IL-2 before IFN-γ conversion by QFT suggests IL-2 is a likely marker of early infection leading to subsequent conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IFN-γ, additional biomarkers have emerged as potential candidates for the evaluation of antigen recognition in whole-blood stimulation assays, such as IP-10, IL1RA, TNF-α and IL17. 14,[17][18][19] This study aimed to evaluate more cytokines as alternative biomarkers of whole-blood stimulation assays in diagnosing nonhuman Panel 1 6 TNF RII, IL19, RANTES, MIF, MPO, Galectin-3 Panel 2 37 IFN-γ, TNF-α, TNF RI, GM-CSF, IL1β, IL1RA, IL1 RII, IL2, IL2 Rα, IL4, IL5, IL6, IL6 Rα, IL8, IL10, IL15, IL17A, IL22, MCP-1, MIP-1β, MCP-3, MCP-4, CCL11, CCL18, CCL22, CCL27, CXCL1, CXCL4, IP-10, CXCL12, CXCL13, CD14, CD27, CD30 been proven to be robust biomarkers of whole-blood stimulation assays. [22][23][24] In our study, IFN-γ and IP-10 were also identified as sensitive markers for the PPD-based whole-blood stimulation assay in nonhuman primates, and IP-10 appeared to be more sensitive than…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection bias was unclear for seven articles (7/18), which used cross-sectional design in six articles and did not report the time of patient selection in one article [25,27,28,30,35,37,38]. In addition, the index tests bias was unclear in 13 articles (13/18), because the results of IL-2 cannot be obtained in blinded conditions [26][27][28][29][30][31][32][33][34][36][37][38][39]. The reference standard bias was unclear for one article (1/18), which had intermediate results 33.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…The reference standard bias was unclear for one article (1/18), which had intermediate results 33. Flow and timing bias were unclear for six articles (6/18), in which patients were lost during the analysis of the diagnostic potential of IL-2 [23,25,28,31,33,37]. The bias of applicability concerns was generally low.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation